Occurrence, associated risk factors and antimicrobial resistance patterns of Staphylococcus aureus and methicillin resistant S. aureus from foods of bovine origin in Dessie and Kombolcha towns, Ethiopia - Abebe, Engidaw; Gugsa, Getachew; Ahmed, Meselu; Awol, Nesibu; Tefera, Yalew; Abegaz, Shimelis (Frontiers in Sustainable Food Systems, 2024)
Food-producing animals including bovine species are major reservoirs for different food-borne pathogens. Staphylococcus aureus is among the leading causes of food-borne diseases globally that can be transmitted mainly through consumption of contaminated foods of animal origin and emergence of multidrug resistant bacteria like methicillin resistant S. aureus (MRSA) become a significant public health concern. A cross-sectional study was conducted from October 2019 to July 2021 to estimate the prevalence, identify associated risk factors and determine antibiogram profiles of S. aureus and MRSA from foods of bovine origin in Dessie and Kombolcha towns. A total of 384 foods of bovine origin samples were collected using random sampling techniques. Isolation and characterization of S. aureus were done according to the standard bacteriological protocols. Agar disc diffusion method was employed to determine the in vitro antimicrobial resistance pattern of S. aureus and MRSA isolates. The collected data were analyzed using descriptive and inferential statistics. The overall prevalence of S. aureus and MRSA were found to be the equal (39.3%). The prevalence of S. aureus was 55.6%, 44.0%, 41.1%, 36.4%, 16.7%, and 0.0% in yoghurt, beef swab, udder milk, carcass swab, tank milk, and cheese samples, respectively. A statistically significant difference was observed in the prevalence of S. aureus among the different sample types (P<0.05). The prevalence of S. aureus in milk samples from cows with and without treatment history was 47.1% and 26.0%, respectively. The difference in the prevalence of S. aureus among treatment history categories was statistically significant (P<0.05). Higher prevalence of S. aureus was recorded in carcass swab samples collected from Dessie town (50.0%), municipal abattoirs (46.7%), slaughtering process with poor hygiene (57.1%); and carcasses slaughtered by butchers with poor hygiene (62.1%). 100.0%, 97.4%, 90.1%, and 74.8% of S. aureus isolates were resistant to Cefoxitin, Penicillin G, Ampicillin, and Nalidixic acid, respectively. 97.43% of S. aureus isolates showed multidrug resistance to three and more than three drugs. To reduce the high magnitude of S. aureus contamination of foods of bovine origin, improvement of cattle health and good hygienic procedures along the production chain should be implemented in the study area.